Evaluation of field efficacy of microbial and chemical insecticides for the management of defoliator pests in castor: EVALUATION OF FIELD EFFICACY OF MICROBIAL AND CHEMICAL INSECTICIDES IN CASTOR - B GEETHA; S R VENKATACHALAM; P DURAIMURUGAN (Journal of Oilseeds Research, 2020)
Field studies were conducted to evaluate the efficacy of microbial and chemical insecticides against castor semilooper (Achaea janata) and tobacco caterpillar (Spodoptera litura) in castor during kharif 2019-20. Bioefficacy of two microbials viz., DOR Bt-127 SC formulation @ 3 ml/l and commercial formulation of Bacillusthuringiensis var. kurstaki @ 1 g/l and chemical insecticides viz., flubendiamide 39.35SC @ 0.2 ml/l and thiodicarb 75WP @ 1 g/l were evaluated against the pests. Comparing all treatments, the newer insecticide, flubendiamide 39.35SC @ 0.2 ml/l recorded significantly lower infestation of semilooper larval population up to 14 days after the spray treatment (DAT) in both first (0.18 larvae/plant) and second spray (0.11 larvae/plant). In microbials, in both first and second spray treatments at 3 DAT, mortality of the semilooper larvae was high with minimum larval population in DOR Bt-127 SC formulation (0.68 larvae/plant). Reduction in S. litura population was also high in flubendiamide 39.35 SC @ 0.2 ml /l spray followed by DOR Bt-127 SC formulation. The defoliation by both the defoliators was less than 10% in flubendiamide sprayed plots after second spray at 14 DAT. In microbial insecticides sprayed plots also the defoliation by both the defoliatorswas low (12.8 to 14.4%). The effect ofspray treatments on the semilooper larval parasitisation by the parasitoid, S. maculipennis recorded that the microbials were very safe and the larval parasitisation was very high in DOR Bt-127 SC formulation (40.2%) and commercial Btk (28.8%) when compared to chemical pesticides (9.2 to 11.6%). Seed yield obtained was high in flubendiamide (1105 kg/ha) and DOR Bt-127 SC formulation (1078 kg/ha) treatments followed by commercial Btk sprayed plots whereas the lowest yield was recorded in untreated control (642 kg/ha). When comparing the cost involved and return, the net return was high in DOR Bt-127 SC (`22,794/ha) and flubendiamide (`22,215/ha) sprayed plots. Highest cost benefit ratio (1:1.96) was realized with DOR Bt-127 SC formulation followed by flubendiamide (1:1.87).